Meningkatkan Keaktifan Siswa dalam Pembelajaran Klasifikasi Makhluk Hidup melalui Game Interaktif Wordwall di Madrasah Aliyah Hidayatul Insan - Muhammad Syaiful Anwar; Noor Hujjatusnaini (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
Biology learning, particularly the topic of the classification of living organisms, is often considered difficult and boring by some students. To address this challenge, a more engaging and interactive approach is needed. One effective solution is to utilize game-based technology, such as Wordwall, which allows students to actively learn through various educational games. This study aims to enhance student engagement in learning the classification of living organisms using interactive Wordwall games. Through a community service method, this activity involved teachers and students from several schools to integrate Wordwall as a learning tool. The interactive games provided by Wordwall include various types of activities, such as puzzles, quizzes, and matching games, designed to help students better understand the concepts of classification of living organisms. The implementation of this program is expected to improve student motivation, involvement, and understanding of the material. Furthermore, it is hoped that the use of this technology will provide a more enjoyable learning experience and increase the effectiveness of classroom learning. The evaluation conducted shows a significant improvement in student engagement, as well as a better understanding of the material compared to traditional teaching methods.